2020
DOI: 10.31616/asj.2019.0183
|View full text |Cite
|
Sign up to set email alerts
|

Management of Traumatic Spinal Fracture in the Coronavirus Disease 2019 Situation

Abstract: The coronavirus outbreak was labeled a pandemic by the World Health Organization in 2020. Patients who require spine surgery should receive coronavirus disease 2019 (COVID-19) screening to prevent nosocomial cross-infection before surgery. However, spine fracture and spinal injury are critical and serious, and there are no standard protocols for management. This article aims to propose a treatment algorithm for the management of traumatic spine fracture during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 6 publications
0
21
0
3
Order By: Relevance
“…We appreciate the letter regarding our manuscript titled "Management of traumatic spinal fracture in the coronavirus disease 2019 situation [1]. " We would like to thank the reader/s for reading our article.…”
Section: Dear Sirmentioning
confidence: 99%
See 3 more Smart Citations
“…We appreciate the letter regarding our manuscript titled "Management of traumatic spinal fracture in the coronavirus disease 2019 situation [1]. " We would like to thank the reader/s for reading our article.…”
Section: Dear Sirmentioning
confidence: 99%
“…1A). The authors recommended full PPE that is composed of fluid-resistant legs with shoe coverings, goggles, safety glasses, a face shield, a double layer of gloves, and a surgical mask that can be used with a standard N95 respirator [1]. A standard N95 respirator protects the wearer from exposure to airborne particles (e.g., dust, mist, fumes, fibers, and bioaerosols, such as viruses and bacteria) or respiratory system [2].…”
Section: Dear Sirmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the article on "Management of traumatic spinal fracture in the coronavirus disease 2019 situation" is very interesting. Sornsa-Ard et al [1] recommended protocols from Thailand for management of the patients. Thailand is the second country that coronavirus disease 2019 (COVID-19) exists and there is already at least one case of COVID-19 in the patient with spine fracture according to local Thai Centers for Disease Control and Prevention report [2].…”
Section: Dear Editormentioning
confidence: 99%